2010
DOI: 10.1055/s-0030-1247607
|View full text |Cite
|
Sign up to set email alerts
|

Reference Range of Embryo Volume by 3-D Sonography Using the XI VOCAL Method at 7 to 10 + 6 Weeks of Pregnancy

Abstract: We sought to establish normative data for three-dimensional ultrasound (3DUS) first-trimester embryonic volume using the extended imaging virtual organ computer-aided analysis (XI VOCAL) technique. This cross-sectional study involved 64 normal pregnancies at 7 to 10 + 6 weeks' gestation. Embryonic volume was obtained on 3DUS using the XI VOCAL technique with manual outline of 10 sequential planes. The mean, median, standard deviation, and maximum and minimum values were obtained for each week calculated. Polyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…Recently, several volume measurements using XI VOCAL technique in the first trimester of pregnancy have been documented. Araujo J unior et al, 8 Nardozza et al, 14 and Florido et al 15 have previously shown that XI VOCAL is a valid, reliable, and repeatable technique for volume measurements of such structures in the first trimester of pregnancy. We also detected good and moderate degrees of agreement in the GS (ICC 5 0.97; 95% CI, 0.88-0.99), placenta (ICC 5 0.94; 95% CI, 0.76-0.99), and in the embryonic (ICC 5 0.67 (95% CI, 0.34-0.92) and amniotic sac (ICC 5 0.65; 95% CI, 0.41-0.91) volume measurements, respectively.…”
Section: Progesterone Increases Endometrial Maturation and Regulates mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several volume measurements using XI VOCAL technique in the first trimester of pregnancy have been documented. Araujo J unior et al, 8 Nardozza et al, 14 and Florido et al 15 have previously shown that XI VOCAL is a valid, reliable, and repeatable technique for volume measurements of such structures in the first trimester of pregnancy. We also detected good and moderate degrees of agreement in the GS (ICC 5 0.97; 95% CI, 0.88-0.99), placenta (ICC 5 0.94; 95% CI, 0.76-0.99), and in the embryonic (ICC 5 0.67 (95% CI, 0.34-0.92) and amniotic sac (ICC 5 0.65; 95% CI, 0.41-0.91) volume measurements, respectively.…”
Section: Progesterone Increases Endometrial Maturation and Regulates mentioning
confidence: 99%
“…It can particularly measure the volume of complex objects easily and accurately. Using this technique in the first trimester of pregnancy was previously described in several studies, [8][9][10][11] and it is possible to detect placental and fetal volumes accurately at this gestational period.…”
Section: Introductionmentioning
confidence: 99%
“…(Εικόνα από http://medison.com.vn/vn/default/Cong-nghe/3dxi/XI-XI-VOCAL.aspx) Βιβλιογραφικά με την μέθοδο XI VOCAL έχει μελετηθεί ο εμβρυικός μηρός [126] , το άνω άκρο [127] , η καρδιά του εμβρύου [128] , ο λεκιθικός ασκός [129], το μέγεθος εμβρύου [130] , τα εμβρυικά νεφρά [131] . Επίσης από τον Barreto EQ, 2010 [132] έγινε σύγκριση των τριών πιο συχνών μεθόδων τρισδιάστατης μέτρησης δηλαδή της multiplanar , της VOCAL και της XI-VOCAL .…”
Section: μετρηση ογκου με την τεχνικη χι Vocalunclassified